Creative Learning Media Management with Canva: Building Teacher Skills in The Digital Age - Anaguna, Nursyam; Arifin, Nurhikma (Jurnal Pengabdian Pada Masyarakat, 2024)
One of the main problems at SDN 7 Ulu Balombong is the lack of teacher skills in integrating technology and utilizing creative learning media to create a learning environment that is motivating and in line with current developments. To solve this problem, community service activities were carried out in the form of training and assistance in using Canva which aimed to help teachers at the school improve their technology integration skills in creative learning. The implementation method used is to adopt the action research stages which consist of 5 stages, namely: planning, action, observation, evaluation and reflection, and mentoring. Training activities are carried out for one day, while mentoring activities are carried out for 2 months. The results of the training showed a significant increase in building teacher skills using the creative learning media Canva where the satisfaction score of the training participants reached the very satisfied category with a percentage of 89.66%. Discussion and observation activities carried out showed an increase in understanding, digital literacy and quality of learning through the use of creative learning media based on Canva technology.